Analysis of Company Capability, Supply Chain Management of Competitive Advantage, and Company Performance - Nuraini Nuraini; Sumitro Sarkum; Abdul Halim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The main purpose of this test is to determine the situation that affects the independent variables like the company's ability, supply chain management practices, supply chain responsiveness, and supply chain strategy regarding competitive advantage which is used as the dependent variable. As well as supply chain management practices on company performance are used as moderating variables at UPPKS ANANDA JAYA. This research uses non-probability sampling analysis method and technical Accidental Sampling, this research was conducted to distributors with a total of 150 respondents. The conclusion of this test shows that the company's performance can develop quality with competitive advantages and supply chain management practices that are met. Likewise, with the capabilities of the company, supply chain responsiveness and supply chain strategies have a positive effect so that companies can increase their competitive advantage. However, it is different in the supply chain management practice variable which cannot develop a competitive advantage in the company. To be able to advance competitive advantage, companies must pay attention to and know the weaknesses that can become problems, it is necessary to have strengths by implementing supply chain management to maintain the company's competitive advantage.